Employment incongruity and gender among Middle Eastern and North African skilled migrants in Australia. (2nd January 2021) - Faaliyat, Negar; Ressia, Susan; Peetz, David
ABSTRACT: We investigate 'employment incongruity' among skilled migrants from Middle Eastern and North African (MENA) countries – that is, whether the jobs they achieve in Australia match the jobs they expect to be doing after they arrive or not – along with the factors that shape outcomes and the gendered dimensions of these outcomes. We analyse data collected from qualitative interviews with 15 females and eight male skilled MENA migrants, a median of seven years after arrival and apply an intersectionality lens and consider influences at the macro, meso and micro level that affect the power of female MENA migrants and shape their employment outcomes. We identify that what appears to shape employment incongruity are: organisational practices regarding recognition of overseas qualifications and demands for 'local experience'; norms supporting discriminatory behaviour; the difficulties skilled MENA migrants have with accessing networks; and intra-family cultural norms. These findings are significant for current and future skilled MENA migrants, with the employment outcomes of most of the participants in this study revealing a mismatch between government immigration policies and organisational practices.